CHARACTERISTICS OF PRACTICAL PHYSICAL DEVELOPMENT OF TEENAGE STUDENTS IN FAMILY-SCHOOL PARTNERSHIP (Conferencea, 2023)
In the article, the practical physical training, physical maturity and physical development of teenage students in family-school cooperation were studied. This scientific-research work covers issues aimed at further improving and developing the knowledge and skills of our adolescent students and their knowledge of physical education culture.